2010
DOI: 10.4085/1062-6050-45.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy and Joint Position Sense in Healthy Participants: A Systematic Review

Abstract: Objective: To (1) search the English-language literature for original research addressing the effect of cryotherapy on joint position sense (JPS) and (2) make recommendations regarding how soon healthy athletes can safely return to participation after cryotherapy.Data Sources: We performed an exhaustive search for original research using the AMED, CINAHL, MEDLINE, and SportDiscus databases from 1973 to 2009 to gather information on cryotherapy and JPS. Key words used were cryotherapy and proprioception, cryoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 47 publications
(102 reference statements)
2
60
0
7
Order By: Relevance
“…(6) The effect of cryotherapy on proprioception, which is a component of the somatosensory system, is still poorly understood. (7) Proprioceptive acuity is defined as the ability of an individual to determine the joint position sense, motion and strength of the limbs. (8) Consequently, the proprioceptive acuity is an essential component for injury prevention and rehabilitation, but is often ignored, with serious consequences, because the proprioceptive deficit can be responsible for many acute joint lesions.…”
Section: Introductionmentioning
confidence: 99%
“…(6) The effect of cryotherapy on proprioception, which is a component of the somatosensory system, is still poorly understood. (7) Proprioceptive acuity is defined as the ability of an individual to determine the joint position sense, motion and strength of the limbs. (8) Consequently, the proprioceptive acuity is an essential component for injury prevention and rehabilitation, but is often ignored, with serious consequences, because the proprioceptive deficit can be responsible for many acute joint lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have investigated the impact of cooling upon JPS 27 , the effect of this intervention upon the accuracy of force reproduction has received less attention 29 . It is likely that the viscoelasticity of tissues, particularly the mechanical property of the tendon, might be changed by cryotherapy, thereby suggesting that decreased compliance with the muscle-tendon unit may directly impair its force-generating capacity and also influence neural activation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Ozmun et al 7) reported that ice bag application to the knee had no effect on proprioception. Furthermore, the potential for cryotherapy to degrade JPS is unknown due to a limited number of publications, as noted in a recent systematic review 8) . Thus, the effects of cryotherapy on JPS are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%